Aerobic Exercise Practiced Over Time Mitigates the Structural Effects on the Vascular System Caused by the Deleterious Effects of Aging - Nicoletti RA; Souza TP; Miotto DS; Duchatsch F; Tardelli LP; de Paula VF; Amaral SL; Zago AS (Vascular Health and Risk Management)
Rafael Antunes Nicoletti,1,2 Thiago Pereira de Souza,1,2 Danyelle S Miotto,3 Francine Duchatsch,3 Lidieli Pazin Tardelli,3 Vinicius Ferreira de Paula,3 Sandra Lia Amaral,1,3 Anderson Saranz Zago1,2 1Department of Physical Education, School of Sciences, Sao Paulo State University (UNESP), Bauru, Brazil; 2Graduate Program in Movement Science, Sao Paulo State University, UNESP, SP, Brazil; 3Joint Graduate Program in Physiological SciencesPIPGCF Ufscar/UNESP, São Carlos, BrazilCorrespondence: Anderson Saranz Zago, Sao Paulo State University (UNESP) – Bauru/São Paulo/Brazil, Tel +55-14-3103-6082 - Extension-9436, Email anderson.zago@unesp.brBackground: Aerobic training has been considered beneficial for determining the detrimental alterations in blood vessels caused by aging.Objective: Evaluate the relationship between the preventive effects of aerobic exercise and time of practice on cardiovascular health, in aged Wistar rats.Methods: Wistar rats (16 months) were divided into 3 groups: (1) sedentary (AGED); (2) long-term trained\61 weeks (LTT); and (3) short-term trained\final 8 weeks of life (STT). Body weight, maximum physical capacity, systolic blood pressure (SBP), pulse wave velocity (PWV), plasma nitrite (NO), oxidative stress (TBARS), wall thickness, the wall-to-lumen ratio, and collagen of the thoracic aorta, carotid, and femoral arteries were measured.Results: Both trained groups showed an increase in physical capacity when compared to the AGED group (p=< 0.001 for LTT and p=0.011 for STT), and the LTT group demonstrated higher values when compared to the STT group (p= 0.004). The LTT group presented attenuation of PWV (p= 0.002) and a reduction in the wall thickness and wall-to-lumen ratio of the thoracic aorta (p=0.032 and 0.008, respectively) and carotid arteries (p=0.019 and 0.012, respectively) when compared to the AGED group. The STT group presented a reduction in TBARS compared to the AGED group (p=0.046). Additionally, both trained groups (LTT and STT) presented a reduction in the percentage of arterial collagen compared to the AGED group in the thoracic aorta (p=< 0.001 and p=0.001 respectively) and carotid arteries (p= < 0.008 and p= 0.041 respectively).Conclusion: This study demonstrated that long-term training decreased the level of collagen, PWV values, wall thickness, and the wall-to-lumen ratio of the aorta and carotid arteries compared to the AGED group. Moreover, short-term training reduced TBARS and collagen percentage in the aorta and carotid arteries compared to the AGED group.Keywords: aging, aerobic training, pulse wave velocity, collagen deposition, arteries